Cyclodextrins in pharmaceutics, cosmetics, and biomedicine : current and future industrial applications - Bilensoy, Erem (Wiley, 2011)
Cyclodextrins in Pharmaceutics, Cosmetics, and Biomedicine covers a wide range of knowledge on cyclodextrins, from an overview of molecular and supramolecular aspects of cyclodextrin physicochemistry, to the latest outcomes in cyclodextrin use and future possibilities in the employment of these systems. This book focuses on the derivatives and physicochemical and biological properties of cyclodextrins, and considers drug delivery through topical, mucosal, and oral via cyclodextrin complexes.- Resumé vydavatel
Keywords: cyklodextriny; farmaceutická technologie; biomedicína; cyclodextrines; pharmaceutical technology; biomedicine; elektronické knihy; sborníky; electronic books; papers of several authors